Alternative splicing control of light and temperature stress responses and its prospects in vegetable crops - Haishun Cao; Tingquan Wu; Liangliang Shi; Li Yang; Changyuan Zhang (Vegetable Research)
Vegetable crop quality and productivity are impaired by adverse light and temperature stresses, such as low light, cold, and heat stress. Alternative splicing is a powerful strategy for coping with these abiotic stresses by producing multiple mRNA splicing variants with different subcellular locations, translation efficiency, and coding sequences. Pre-mRNA is alternatively spliced by the spliceosome consisting of different splicing-related proteins termed splicing factors. Recent studies have shown that splicing factors and splicing variants have diverse effects on the development, flowering, and fertility of model plants under light and temperature stresses, but there is very little information available for vegetable crops. Therefore, we conducted a comprehensive literature review on the roles of alternative splicing in regulating plants' responses to light and temperature stress. Several suggestions for future studies and implementation in the field of vegetable crops are presented. We can manipulate alternative splicing using CRISPR/Cas9 technology to produce splicing variants with diverse roles for improving performance of vegetable crop under stress environments.